Controllable and Scale-Up Synthesis of Nickel-Cobalt Boride@Borate/RGO Nanoflakes via Reactive Impingement Mixing: A High-Performance Supercapacitor Electrode and Electrocatalyst - Qian, Yudan; Wu, Yechao; Gu, Fan; Zhou, Zhiming; Huang, Zaimei; Tang, Xinyue; Pan, Shuang; Zhang, Shangcong; Chen, Shinan; Zhang, Qingcheng; Chen, Yihuang; Wang, Shun (Frontiers in Chemistry, 2022)
Large-scale synthesis of graphene-based nanomaterials in stirred tank reactor (STR) often results in serious agglomeration because of the poor control during micromixing process. In this work, reactive impingement mixing is conducted in a two-stage impinging jet microreactor (TS-IJMR) for the controllable and scale-up synthesis of nickel-cobalt boride@borate core-shell nanostructures on RGO flakes (NCBO/RGO). Benefiting from the good process control and improved micromixing efficiency of TS-IJMR, NCBO/RGO nanosheet provides a large BET surface area, abundant of suitable mesopores (2–5 nm), fast ion diffusion, and facile electron transfer within the whole electrode. Therefore, NCBO/RGO electrode exhibits a high specific capacitance of 2383 F g-1 at 1 A g-1, and still retains 1650 F g-1 when the current density is increased to 20 A g-1, much higher than those of nickel boride@borate/RGO (NBO/RGO) and cobalt boride@borate/RGO (CBO/RGO) synthesized in TS-IJMR, as well as NCBO/RGO-S synthesized in STR. In addition, an asymmetric supercapacitor (NCBO/RGO//AC) is constructed with NCBO/RGO and activated carbon (AC), which displays a high energy density of 53.3 W h kg-1 and long cyclic lifespan with 91.8% capacitance retention after 5000 charge-discharge cycles. Finally, NCBO/RGO is used as OER electrocatalyst to possess a low overpotential of 309 mV at a current density of 10 mA cm-2 and delivers a good long-term durability for 10 h. This study opens up the potential of controllable and scale-up synthesis of NCBO/RGO nanosheets for high-performance supercapacitor electrode materials and OER catalysts.